Relationship between life satisfaction and academic achievement among trainee teachers / Azyyati Zakaria and Nur Hazwani Abdul Halim - Zakaria, Azyyati; Abdul Halim, Nur Hazwani (Penerbit UiTM (UiTM Press), 2017)
Life satisfaction is a way a person evaluates his or her life and how he or she feels about where it is going in the future. This study was conducted to investigate the level of high achievers’ life satisfaction, the domains of their life satisfaction and its relationship to their academic achievement. Based on the literature review, academic achievement is predicted to contribute significantly to high level of life satisfaction compared to other domains in life. Forty-five (45) high-achieving (those who obtained a CGPA of 3.50 to 3.99) students have participated in this study. This study is adapted from a research of Diener et al. (1985) on Extended Satisfaction with Life Scale (ESWLS). Four domain factors, namely social, self, physical and family were studied. Both descriptive and inferential statistics were used in this study. The results showed that the high-achieving students showed a high level of life satisfaction in terms of family supports domains but moderate level of satisfaction on their appearance. Nevertheless, for various reasons, academic satisfaction is not a strong determinant of their life satisfaction.